2016
DOI: 10.1098/rsos.160580
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nitride supported copper nanoparticles: light-induced electronic effect of the support for triazole synthesis

Abstract: The composite framework of graphitic carbon nitride (gCN) supported copper nanoparticle can act as a high-performance photoreactor for the synthesis of 1,2,3-triazole derivatives under light irradiation in the absence of alkaline condition. The photoactivity of gCN originates from an electron transition from the valence band to the conduction band, in the presence of photon energy, and the hot electron acts as a scavenger of the terminal proton of the alkyne molecule to facilitate the formation of copper aceta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Various solid materials, such as carbon, clay, and metal oxide, have also been employed as a support system for the metal catalysts where strong metalsupport interaction prevents the metal-metal interaction and seizes the agglomeration process. In our earlier studies, we showed the carbon nitride (CN) could also act a successful support material for the metal catalyst for various heterogeneous reactions [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Various solid materials, such as carbon, clay, and metal oxide, have also been employed as a support system for the metal catalysts where strong metalsupport interaction prevents the metal-metal interaction and seizes the agglomeration process. In our earlier studies, we showed the carbon nitride (CN) could also act a successful support material for the metal catalyst for various heterogeneous reactions [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Copper serves as a catalyst for the title reaction, whereas MPEG scavenges the free‐radicals with the formation of stable carbon‐centered free‐radicals that abstract the H‐atom from the alkyne molecule by means of a hydrogen atom transfer mechanism, and finally proceed for the triazole product in the presence of an azide molecule. In association with our ongoing research on the fabrication of effective catalysts for the cyclo‐addition of azide and alkyne molecules, further efforts will undertake in future for the development of new materials as catalyst to perform the similar kind of reactions by involving the heterocycle substituted azide molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the light excitation, the conduction band electron of the Cu (I) sulfide quantum dot acts as a scavenger of the terminal proton of the alkyne in the presence of organic azide with the formation of 1,4‐disubstituted 1,2,3‐triazoles, where the Cu (I) species of Cu 2 S acts as a catalyst for the reaction . We also have demonstrated that the composite of copper nanoparticles and carbon nitride performs as an effective system for the cycloaddition reaction between azide and alkyne molecules under UV‐radiation conditions where copper nanoparticles serve as active catalyst and the photoactive support material (carbon nitride) plays the role of a promoter …”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Due to these merits, carbon nitride (CN) has been applied as a support material for a wide-range of inorganic nanomaterials for diverse applications. 24 However, the application of carbon nitride for the fabrication of resistive random-access memory (RRAM) devices has rarely been reported. A device made with CN powder, as an active layer, was reported for RRAM applications with a switching ratio o100.…”
Section: Introductionmentioning
confidence: 99%